Importance of Temporary Architecture and Permanence as an Obsolete Notion - Soylu, Çisem (My University, 2018)
Permanence is one of the qualities that has been attributed to architecture since the early ages of human settlements for several reasons such as economical, religious or nationalistic motivations. However, the paradigm shift that accompanied modernism has changed the ways that humankind lives and produces; the phenomena of obsolescence has emerged and new economical approaches as well as daily practices have shifted to a short- termed perception of time and the pace of change has accelerated. Creative destruction has become the fundamental point of origin to the modern design and construction practices. Primarily investigating the meaning of permanence -absolute and relative permanence- and the drivers of building permanent structures based on the value of architecture both theoretically and historically, this study aims to examine the obtrusive conflict between the modern transformation towards short-termism and the building culture that remained solid in terms of temporaryness. Initiations for discovering ways of building temporary structures or applying short-termed or reusable materials have great importance today, although many examples of temporary architecture may be seen throughout the history of humankind, for a more sustainable, mobile and humble architecture. The conclusion objective of this paper is to track the first modern responses to the interchangeable urban texture during the second half of the twentieth century and how the idea has evolved in time, arriving to the recent applications of temporary modals in the means of structure and material. It is crucial that architecture adapts to this relatively new conjuncture as building life spans are dramatically decreasing and natural resources are at critical levels and temporary structures may be the answer.
Keywords: Permanence; Obsolescence; Creative Destruction; Temporary Architecture